COMBINED THERAPY WITH DONEPEZIL AND MEMANTINE IN THE TREATMENT OF MODERATE TO SEVERE ALZHEIMER'S DISEASE - Cerchiari, Isabela; Gardenal, Clicia Ferreira; dos Santos, Taynara Maria Gomes; Rocha, Beatriz Oliveira; Valejo, Alana Alves Ibanhes; Jordão, Nicole Oliveira; Rodrigues, Milene Márcia de Faria; Pedrazzi, Luiza Antonello; Fechine, Maria Auxiliadora Bezerra; Oliveira, Michell Ícaro Lima; Barsella, Augusto Rafael; Passos e Silva, Leandra dos; et al. (Seven Editora, 2026)
Alzheimer’s disease is a progressive neurodegenerative disorder characterized by cognitive, behavioral, and functional decline, particularly in moderate to severe stages. In this context, combination therapy with donepezil, an acetylcholinesterase inhibitor, and memantine, an NMDA receptor antagonist, has been proposed as a therapeutic strategy to enhance clinical outcomes. This study aims to analyze the efficacy and safety of this combination in the treatment of moderate to severe Alzheimer’s disease. This is an integrative literature review with a qualitative and descriptive approach, based on studies retrieved from PubMed, SciELO, LILACS, covering publications from 2016 to 2026. The findings indicate that combination therapy provides superior benefits compared to monotherapy in terms of cognition, daily functioning, and behavioral symptoms, although clinical gains are generally modest. A favorable safety profile and potential cost-effectiveness were also observed, particularly in public healthcare settings. It is concluded that the association of donepezil and memantine is a valid therapeutic option, and its use should be individualized according to patient clinical characteristics.